Ab Initio and Semiempirical Computational Studies on 1-{(2E)-2-[(Aminocarbonothioyl)hydrazono]-2-(3-mesityl-3-methylcyclobutyl)ethyl}-pyrrolidine-2,5-dione - Karakurt, Tuncay; Dincer, Muharrem; Cukurovali, Alaaddin (Wiley, 2012)
The molecular geometry, vibrational frequencies, and gauge including atomic orbital (GIAO) (1)wH- and C-13 NMR chemical shift values of the title compound in the ground state have been calculated using the Hartree-Fock (HF) and density functional theory (DFT) methods with 6-31G(d) basis sets, and compared with the experimental data. The calculated results show that the optimized geometries can well reproduce the crystal structural parameters and the theoretical vibrational frequencies, and H-1- and C-13 NMR chemical shift values show good agreement with experimental data. To determine conformational flexibility, the molecular energy profile of the title compound was obtained by semiempirical (AM1) calculations with respect to the selected torsion angle, which was varied from -180 degrees to +180 degrees in steps of 10 degrees. The energetic behavior of the title compound in solvent media was examined using the B3LYP method with the 6-31G(d) basis set by applying the Onsager and the polarizable continuum model (PCM). The results obtained with these methods reveal that the PCM method provided more stable structure than Qnsager's method. By using TD-DFT method, electronic absorption spectra of the title compound have been predicted and a good agreement with the TD-DFT method and the experimental one is determined. The predicted nonlinear optical properties of the title compound are much greater than ones of urea. In addition, the molecular electrostatic potential (MEP), frontier molecular orbitals (FMO) analysis, NBO analysis and thermodynamic properties of the title compound were investigated using theoretical calculations. (C) 2011 Wiley Periodicals, Inc. Int J Quantum Chem 112: 394-413, 2012
Keywords: IR and NMR spectroscopy; Onsager; ab initio calculations; electronic structure